2020
DOI: 10.20527/dentino.v5i2.8970
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF Musa acuminata AND Ocimum basilicum MIXED EXTRACTS TO THE SURFACE HARDNESS OF BIOACTIVE COMPOSITE RESIN

Abstract: Backgrounds: The use of mouthwash daily may influence the mechanical properties of bioactive composite resin as a dental restoration, one of the mechanical properties is surface hardness. Herbal mouthwash can be used to minimize the side effect of mouthwash that contain alcohol. Mauli banana stem and basil leaf extracts can be produced into herbal mouthwash. Methods: Thirty specimens (10mm diameter x 2mm thick; n=5/group) bioactive composite resins were immersed in a mixed solution of Mauli banana and basil le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Hardness is also used as an indirect method of measuring the DC; the higher the conversion rate, the higher the hardness value. 31,32 The initial results of microhardness in the conventional and bulk-fill RBCs in this study were similar, which may have been due to the loading of similar filler content in these 2 types of composites. The results of the studies by Ilie et al 9 and Puspitasari et al 31 demonstrated that some bulk-fill RBCs show less hardness than conventional RBCs with the same filler content.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Hardness is also used as an indirect method of measuring the DC; the higher the conversion rate, the higher the hardness value. 31,32 The initial results of microhardness in the conventional and bulk-fill RBCs in this study were similar, which may have been due to the loading of similar filler content in these 2 types of composites. The results of the studies by Ilie et al 9 and Puspitasari et al 31 demonstrated that some bulk-fill RBCs show less hardness than conventional RBCs with the same filler content.…”
Section: Discussionsupporting
confidence: 57%
“…31,32 The initial results of microhardness in the conventional and bulk-fill RBCs in this study were similar, which may have been due to the loading of similar filler content in these 2 types of composites. The results of the studies by Ilie et al 9 and Puspitasari et al 31 demonstrated that some bulk-fill RBCs show less hardness than conventional RBCs with the same filler content. This difference is related to the presence of pre-polymerized organic fillers in addition to inorganic fillers in these materials.…”
Section: Discussionsupporting
confidence: 57%
“…cual el yeso incorpora suficiente vapor de agua para iniciar la reacción del fraguado, por una proporción polvo/ agua; alterada 20 .…”
Section: Discussionunclassified
“…La muestra fue posicionada lo más cerca posible a la base, formando un ángulo de 90°. Luego, el sistema se activó a una velocidad de 2 mm/min con fuerza en la misma dirección, pero en diferente sentido hasta que ocurrió la fractura de la muestra [20][21][22][23][24] (Figura 4).…”
Section: Materiales Y Métodosunclassified